Boron-doped diamond nanowire array electrode with high mass transfer rates in flow-by operation. Issue 20 (20th March 2018) - Lee, Choong-Hyun; Lim, Young-Kyun; Lee, Eung-Seok; Lee, Hyuk-Joo; Park, Hee-Deung; Lim, Dae-Soon
Abstract : We fabricated a boron-doped diamond nanowire (BDDNW) array electrode via lithography and metal-assisted chemical etching (MACE) to provide a highly promoted surface area and increased mass transport during the electrochemical oxidation process. Abstract : We fabricated a boron-doped diamond nanowire (BDDNW) array electrode via soft lithography and metal-assisted chemical etching (MACE) of Si to provide a highly promoted effective surface area and increased mass transport during the electrochemical oxidation process. The effects of aligning the BDDNW on the electrochemical oxidation performance and the current efficiency of the electrode in phenol oxidation were examined. Although the effective surface area of the BDDNW array with an aligned nanowire configuration was smaller than that of the BDDNW with a random nanowire configuration, the BDDNW array electrode exhibited a higher mass transfer coefficient, resulting in a better performance in the removal of phenol. The enhanced mass transport exhibited by the BDDNW array electrode also greatly enhanced the chemical oxygen demand (COD) and current efficiency. Furthermore, because of its excellent oxidation performance, the BDDNW array electrode also exhibited much lower energy consumption during the phenol oxidation process.